PENDEKATAN SAVI TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK TUNAGRAHITA RINGAN DI SLB Â - Annisah, Khoirun (Jurnal Pendidikan Khusus, 2017)
ABSTRACT   This research about the influence of SAVI approach toward beginning reading ability to mild mentally retardation children was formed background by the hindrance of beginning reading of mild mentally retardation children. It was caused by less interesting learning in the school so that they were given fun learning through SAVI approach which had never been done before. The purpose of this research was to observe the influence of SAVI approach toward beginning reading ability to mild mentally retardation children. The research method used in this research was quantitative approach of pre experimental design kind with the arrangement of one group pre test-post test design. The statistic technique in the data analysis of this research was Wilcoxon matched pairs test. The data collection technique was in the form of test, observation, and documentation. The research indicated that before giving treatment the beginning reading ability of mild mentally retardation children had average value 39,28 and after giving treatment it enhanced to be 62,50. The research indicated that the value of Z counted (Zh) = 2,5 was greater than critic value of Z table 5% (Zt) = 2 (Zh > Zt) so Ho was refused Ha was accepted so that there was influence of SAVI approach toward beginning reading ability to mild mentally retardation.   Keywords: beginning reading, SAVI